2007
DOI: 10.1111/j.1365-2672.2007.03328.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and strain diversity of thermophilic campylobacters in cattle, sheep and swine farms

Abstract: Aims:  To determine prevalence and strain diversity of thermophilic campylobacters in healthy ruminants and swine. Methods and Results:  Faecal samples collected from 343 herds (120 sheep, 124 beef cattle, 82 dairy cattle and 17 swine) in the Basque Country were screened in pools for thermophilic campylobacters. Two hundred and three herds were positive (67·1% dairy cattle, 58·9% beef cattle, 55·0% sheep and 52·9% pig), and species‐specific PCR identified Campylobacter jejuni in 20·7% of the herds and Campylob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
81
5
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 35 publications
(81 reference statements)
12
81
5
2
Order By: Relevance
“…Chickens are not the main host for C. coli, which shows a preference for swine or cattle (Botteldoorn et al, 2001;Oporto et al, 2007), although some studies have shown that C. coli is capable of colonizing chickens efficiently (Bull et al, 2006;Miller et al, 2006). This fact is proven in our study, in which C. coli appeared in a higher percentage of chickens than C. jejuni.…”
Section: Discussionsupporting
confidence: 76%
“…Chickens are not the main host for C. coli, which shows a preference for swine or cattle (Botteldoorn et al, 2001;Oporto et al, 2007), although some studies have shown that C. coli is capable of colonizing chickens efficiently (Bull et al, 2006;Miller et al, 2006). This fact is proven in our study, in which C. coli appeared in a higher percentage of chickens than C. jejuni.…”
Section: Discussionsupporting
confidence: 76%
“…In most of the studies in both countries, C. jejuni accounted for the majority of Campylobacter detected in farm animals including pigs. These findings in pigs contradict those of other studies which indicated that Campylobacter infections in pigs show a dominance of C. coli [73][74][75][76]. Nevertheless, the finding is supported by some other studies which have found a dominance of C. jejuni in pigs [77,78].…”
Section: Thermophilic Campylobacter In Poultrycontrasting
confidence: 57%
“…Campylobacter spp. can be found in the intestinal tract of a wide variety of wild and domesticated animals without any obvious clinical symptoms [11,19,24]. Thus, the major transmission route of infection is hypothesized as the ingestion of food of animal origins, in particular consumption of undercooked poultry, and secondary contaminated foods [23].…”
mentioning
confidence: 99%